2012
DOI: 10.1007/s10114-012-0617-y
|View full text |Cite
|
Sign up to set email alerts
|

Multilinear fractional integrals on Morrey spaces

Abstract: In the present paper we obtain and extend the boundedness property of the Adams type for multilinear fractional integral operators. Also, we deal with the Olsen type inequality.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
8
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 19 publications
2
8
0
Order By: Relevance
“…where A i ∈ BMO(R n ). Then we conclude that our results improve [23,Theorem 7.2] and [38,Theorem 1.1].…”
Section: Corollary 15 (The Spanne Type Estimate For Isupporting
confidence: 80%
See 2 more Smart Citations
“…where A i ∈ BMO(R n ). Then we conclude that our results improve [23,Theorem 7.2] and [38,Theorem 1.1].…”
Section: Corollary 15 (The Spanne Type Estimate For Isupporting
confidence: 80%
“…where A i ∈ BMO(R n ). Then we conclude that our results improve [23,Theorem 7.2] and [38,Theorem 1.1]. Remark 1.10 As far as we know, Theorem 1.1 is also a new result even if we take m = 1 .…”
Section: Remark 19 Theorem 11 Is Also True If We Takesupporting
confidence: 68%
See 1 more Smart Citation
“…Moreover, the Morrey spaces boundedness of I α was discussed by some authors, see [39,62] and [63], for example. In 2012, Iida et al [40] gave a result, where the range of indexes is sharp.…”
Section: Bilinear Fractional Integral Operatorsmentioning
confidence: 98%
“…As is well known, the boundedness of the classical operators in the harmonic analysis on the weighted Morrey spaces has extensively been studied (see [2][3][4][5][6] and references therein). In particular, Wang and Yi [6] recently showed that the -linear commutators and the iterated commutators of the -linear Calderón-Zygmund operators are bounded on weighted Morrey spaces.…”
Section: Introductionmentioning
confidence: 99%